Direct-Acting Antivirals in the Treatment of Hepatitis C Virus Recurrence after Liver Transplantation: Real-life Experience in a Mexican Cohort - Kauffman-Ortega, Eric; Ruiz-Manriquez, Jesus; Olivas-Martinez, Antonio; Campos-Murguía, Alejandro; Flores-García, Nayelli C; Márquez-Guillén, Ernesto; López-Yáñez, Silvia; Sánchez-Ávila, Francisco; Toapanta-Yanchapaxi, Liz; Paez-Zayas, Victor M; García-Juárez, Ignacio (Archives of medical research, 2021)
Hepatitis C virus (HCV) infection is one of the most frequent causes of liver transplantation (LT) worldwide. Patients with HCV viremia at the time of LT universally develop recurrent HCV in the allograft, leading to accelerated fibrosis and graft loss. Treatment with direct-acting antivirals (DAA) is highly effective and safe in this population. To describe the efficacy and safety of DAA in treating post LT HCV recurrence in a Mexican cohort. Methods: We designed a retrospective cohort study that included all LT patients from 2000–2019 with HCV recurrence after LT who received DAA. Clinical and biochemical characteristics were collected from clinical records. Patients who received treatment before LT and those who received interferon-based therapies after LT achieving sustained viral response at 12 weeks were excluded; patients who didn´t complete DAA therapy were eliminated. The primary outcome was SVR-12. Results: Fifty-six patients received DAA after the LT with 98% SVR-12. The most frequent genotypes were 1b (54%) and 1a (34%). The most common antiviral scheme used was sofosbuvir/ledipasvir for 12 weeks in 59% of the patients. No severe adverse effects were observed. Ribavirin was used in 82% of the patients, of which 23.9% had adverse effects, mostly mild. The median follow-up after LT was 55 months (IQR 43-51), with a global and graft survival at one and three years of 100%. Conclusion: In a Mexican cohort, DAA therapy in LT patients with recurrence of HCV infection showed high efficacy and an acceptable safety profile.